ANFÍBIOS (ANURA E GYMNOPHIONA) DO REFÚGIO DE VIDA SILVESTRE “MATAS DO SISTEMA GURJAÚ”, ESTADO DE PERNAMBUCO, NORDESTE DO BRASIL - Santos, José Ricardo Oliveira; Oitaven, Leonardo Pessoa Cabus; Araújo, Alan Pedro de; Moura, Geraldo Jorge Barbosa de (Revista Nordestina de Zoologia, 2016)
The greatest diversity of anurans occurs in the neotropical region, mainly in Brazil, due to the irregularities presented in the relief of each region of the country, which favors microclimates and the speciation of these organisms. The species list is the first step in monitoring biodiversity, contributing to the knowledge about the natural history of the species, and providing data for the creation of conservation measures. Through the above, we aimed to inventory the amphibian fauna at the "Matas do Sistema Gurjaú" a Wildlife Refuge, remnant of the Atlantic Forest located in the Zona da Mata Sul in the state of Pernambuco. The sampling was carried out between January and December 2003 through the active collection method, recording species resulting from visual and auditory recording. There were 41 species of amphibians, 40 anurans and one gymnophiona. The highest species richness was from the Hylidae family (20 spp.) followed by the Leptodactylidade family (7 spp.), evidencing the great distribution of the species of these families by the neotropical region. We registered two species of anurans classified as Vulnerable-VU (Frostius pernambucencis and Agalychinis granulosa), both in the international (IUCN), national (MMA-SISBIO) and state list (Resolution Nº 01 of 09/01/15). The other species of amphibians (95%) are classified as of little concern-LC in all spheres of evaluation. Thus, the construction of a list of species, such as amphibians, remains as one of the main alternatives for the knowledge about the real biodiversity, and its conservation status.